Dynamics of EU food safety certification: a survival analysis of firm decisions - Catherine Ragasa; Suzanne Thornsbury; Satish Joshi (Agricultural and Food Economics, 2017)
The article empirically examines the timing of initial decisions to adopt food safety systems and subsequent decisions to maintain the certification. Survival models are used to evaluate firm-level decisions among seafood processors in the Philippines. Whereas initial certification decisions were influenced mainly by easily obtainable a priori indicators such as output price, scale of production, and association membership, decisions to continue certification were influenced by a larger number of less-visible factors including price differentials across markets and cost structures. Managerial hubris may have played a role in initial certification decisions, but decertification decisions were more informed by realized cost-benefit comparisons. Results highlight tendencies to initially overestimate of benefits and underestimate costs of food safety certifications, resulting in unrealistically optimistic projections and may lead to adverse firm performance.
Keywords: Q18; Q13; D22; L66; 330; HACCP; Food safety; Survival analysis; Seafood industry